The Immunologic Relationship between Root Resorptions and Osteoclastic Activity - Literature Review - Luciano Silva; Alexandrino Pereira dos Santos Neto; Ana Paula Sobral (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2016)
Current literature indicates the close relationship between root resorptions and the role of clasts responsible for hard tissue destruction. The process is complex and involves mechanical factors and intense biological activity. Immunological interactions stimulate the recruitment and migration of clasts into a specific area, in order to destroy bone, cementum and dentin. Nevertheless, understanding the whole process will bring light to other questions concerning the role of the immunologic system in other parts of the human body. The aim of this review was to describe the development of the process, from mineralization to the destruction of hard tissues and the possible relationship between root resorption and cellular immune system.